2021
DOI: 10.18502/ajmb.v13i3.6370
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Drug Discovery to Combat COVID-19 by Repressing Important Virus Proteins Involved in Pathogenesis Using Medicinal Herbal Compounds

Abstract: Background: The cause of COVID-19 global pandemic is SARS-CoV-2. Given the outbreak of this disease, it is so important to find a treatment. One strategy to cope with COVID-19 is to use the active ingredients of medicinal plants. In this study, the effect of active substances was surveyed in inhibiting four important druggable targets, including S protein, 3CLpro, RdRp, and N protein. RdRp controls the replication of SARS-CoV-2 and is crucial for its life cycle. 3CLpro is the main protease of the virus and cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Furthermore, pre-treatments of cells do not block virus infectivity, arguing against a Hypericum perforatum -mediated blockade of the SARS-CoV-2 receptor ACE2. On the other hand, potential modes of antiviral actions of Hypericum perforatum against SARS-CoV-2 were introduced, since hypericin and pseudohypericin were anticipated, by molecular docking, to form a stable complex with the main (3CL) protease or the RNA polymerase of the SARS-CoV-2 [ 62 , 63 ] or had a high affinity toward SARS-CoV-2 basic proteins [ 64 ] but with only little clarification about biological evidence so far. However, it was found that some plant polyphenols could inhibit the 3CL protease using certain experimental settings [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pre-treatments of cells do not block virus infectivity, arguing against a Hypericum perforatum -mediated blockade of the SARS-CoV-2 receptor ACE2. On the other hand, potential modes of antiviral actions of Hypericum perforatum against SARS-CoV-2 were introduced, since hypericin and pseudohypericin were anticipated, by molecular docking, to form a stable complex with the main (3CL) protease or the RNA polymerase of the SARS-CoV-2 [ 62 , 63 ] or had a high affinity toward SARS-CoV-2 basic proteins [ 64 ] but with only little clarification about biological evidence so far. However, it was found that some plant polyphenols could inhibit the 3CL protease using certain experimental settings [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, a review by Cochrane concluded that the results using plant extracts of HP were superior to placebo in patients with major depression, and were equally effective as standard antidepressants with fewer side effects [ 22 , 23 ]. Also, antioxidant, vasoprotective, anticarcinogenic, and antiviral properties of HP have been described [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, N and S proteins are responsible for SARS-CoV-2 assembly and attachment, respectively. Molecular docking outcomes of the study revealed that LN, amentoflavone, (-)-catechin gallate, and hypericin had an affinity for these basic proteins, which possess an effective role in SARS-CoV-2 infection [123].…”
Section: Perspectives Anti-sars-cov-2 (Covid-19) Effectmentioning
confidence: 97%